Encapsulation of honokiol into self-assembled pectin nanoparticles for drug delivery to HepG2 cells. (20th November 2015) - Zhang, Yuxia; Chen, Tong; Yuan, Pei; Tian, Rui; Hu, Wenjing; Tang, Yalan; Jia, Yuntao; Zhang, Liangke
Highlights: Pectin nanoparticles were prepared without using any surfactant and organic solvent. Honokiol, a hydrophobic drug, was encapsulated into pectin nanoparticles. Drug-loaded pectin nanoparticles generated higher cytotoxicity than free honokiol on HepG2 cells. Abstract: Self-assembled pectin nanoparticles was prepared and evaluated for delivering the hydrophobic drug, honokiol (HK), to HepG2 cells. These hydrophobic drug-loaded nanoparticles were developed without using any surfactant and organic solvent. Hydroxypropyl-β-cyclodextrin (HCD) was used to fabricate an inclusion complex with HK (HKHCD) to increase the solubility of the drug and thus facilitate its encapsulation and dispersion in the pectin nanoparticles. Investigation of the in vitro release indicated that the drug-loaded nanoparticles exhibited a higher drug release rate than free honokiol and an effective sustained-release. Cytotoxicity, cell apoptosis and cellular uptake studies further confirmed that the pectin nanoparticles with galactose residues generated higher cytotoxicity than free honokiol on HepG2 cells which highly expressed asialoglycoprotein receptors (ASGR). Nevertheless, these findings were not observed in ASGR-negative A549 cells under similar condition. Therefore, pectin nanoparticles demonstrated a specific active targeting ability to ASGR-positive HepG2 cells and could be used as a potential drug carrier for treatment of liver-related tumors.